Cyclic Neutropenia and Severe Congenital Neutropenia in Patients with a Shared ELANE Mutation and Paternal Haplotype: Evidence for Phenotype Determination by Modifying Genes - Newburger, Peter E. (2010)
BACKGROUND: Cyclic neutropenia (CN) and severe congenital neutropenia (SCN) are disorders of neutrophil production that differ markedly in disease severity. Mutations of the ELANE gene (the symbol recently replacing ELA2) are considered largely responsible for most cases of CN and SCN, but specific mutations are typically associated with one or the other PROCEDURE: We performed ELANE genotyping on all individuals and paternal sperm in an SCN kindred with 8 SCN progeny of a sperm donor and 6 different mothers. RESULTS: One patient with CN had the same S97L ELANE mutation as seven patients with the SCN phenotype. The mutant allele was detected in the donor’s spermatozoa, representing 18% of the ELANE gene pool, but not in DNA from his lymphocytes, neutrophils, or buccal mucosa, indicating gonadal mosaicism. CONCLUSIONS: The coexistence of CN and SCN phenotypes in this kindred with a shared paternal haplotype strongly suggests both a role for modifying genes in determination of congenital neutropenia disease phenotypes, and the classification of CN and SCN within a spectrum of phenotypes expressing varying degrees of the same disease process.